Guanine crystal formation by the unicellular organism Phacotus lenticularis is part of a cellular stress response - Noy Shaked; Andrea Sorrentino; Neta Varsano; Sefi Addadi; Ziv Porat; Iddo Pinkas; Steve Weiner; Lia Addadi (PLoS ONE, 2025)
Organic crystals, and in particular guanine crystals, are widely used by multicellular organisms for manipulating light and producing structural colors. Many single celled eukaryotic organisms also produce organic crystals, and guanine is the most abundant type produced. Their functions are thought to be related to the fact that guanine is nitrogen rich. Here we studied a freshwater unicellular eukaryotic alga, Phacotus lenticularis, and found that when the growth medium is depleted in phosphorus, the alga stops reproducing and produces intracellular birefringent particles inside vesicles. Cryo-SEM showed that these particles are faceted and are located within membranes inside the cell. Using Raman spectroscopy, we showed that these particles are β-guanine crystals. 3D tomograms produced using cryo-soft-X-ray-microscopy quantitatively documented the increase in cell volume and distribution of guanine crystals within the cells with increasing time of phosphorous deprivation. The tomograms also showed additional morphological changes in other cellular organelles, namely starch granules, chloroplasts, nuclear DNA and membranes. The combined observations all indicate that under phosphorous depletion, the algal cells undergo a massive stress response. As guanine crystal formation is part of this response, we conclude that guanine crystals are formed in response to stress, and this is not related to nitrogen availability. Upon addition of phosphate to the P-depleted media, the algal cells, with their guanine crystals, resume reproduction. From this we conclude that the guanine crystals somehow contribute to the recovery from stress.